Antioxidant intake from diet and supplements and risk of digestive cancers in middle-aged adults: results from the prospective NutriNet-Santé cohort. Issue 7 (20th September 2017) - Egnell, Manon; Fassier, Philippine; Lécuyer, Lucie; Gonzalez, Rebeca; Zelek, Laurent; Vasson, Marie-Paule; Hercberg, Serge; Latino-Martel, Paule; Galan, Pilar; Druesne-Pecollo, Nathalie; Deschasaux, Mélanie; Touvier, Mathilde
Abstract: Experimental studies suggest beneficial effects of antioxidants in digestive cancer prevention. However, epidemiological results are contrasting and few studies quantitatively assessed supplemental intake. This study aimed at investigating the associations between antioxidant intakes (dietary, supplemental and total) and digestive cancer risk. This prospective study included 38 812 middle-aged subjects (≥45 years) from the NutriNet-Santé cohort (2009–2016). Dietary data were collected using repeated 24 h records. A specific questionnaire assessed dietary supplement use over a 12-month period. A composition database of about 8000 dietary supplements was developed. Associations between continuous and sex-specific quartiles of vitamins C and E, β -carotene and Se intakes and digestive cancer risk were characterised using multivariable Cox proportional hazard models. A total of 167 incident digestive cancers (120 colorectal, twenty-six pancreatic, nine oesophagus, seven stomach and five liver) were diagnosed during follow-up investigation. Dietary (hazard ratios (HR)Q4 v . Q1 =0·56; 95 % CI 0·34, 0·91, P trend =0·01) and total (HRQ4 v . Q1 =0·51; 95 % CI 0·30, 0·84, P trend =0·008) vitamin C intakes, dietary (HRQ4 v . Q1 =0·56; 95 % CI 0·34, 0·92, P trend =0·005) and total (HRQ4 v . Q1 =0·58; 95 % CI 0·36, 0·94, P trend =0·003) vitamin E intakes, and dietary (HRfor an increment of 10 µg/d= 0·92; 95 % CI 0·85, 1·00, P =0·04) and total (HRfor an increment of 10 µg/d= 0·92; 95 % CI 0·86, 0·99, P =0·03) Se intakes were associated with a decreased digestive cancer risk. Statistically significant interactions were observed between dietary and total Se intakes and alcohol consumption as well as between total vitamin E intake and smoking status. This prospective cohort study with quantitative assessment of supplemental intakes suggests a potential protective effect of several antioxidants (vitamins C and E and Se) on digestive cancer risk, and a modulation of some of these relationships by alcohol consumption and smoking status.